Highest Solar-to-Hydrogen Conversion Efficiency in Cu2ZnSnS4 Photocathodes and Its Directly Unbiased Solar Seawater Splitting - Muhammad Abbas; Shuo Chen; Zhidong Li; Muhammad Ishaq; Zhuanghao Zheng; Juguang Hu; Zhenghua Su; Yanbo Li; Liming Ding; Guangxing Liang (Nano-Micro Letters)
Highlights A novel approach, precursor seed layer engineering, is applied to prepare Cu2ZnSnS4 (CZTS) light-absorbing films using the solution-processed spin-coating method. Mo/CZTS/CdS/TiO2/Pt photocathode effectively mitigates defects in CZTS light absorber and the CZTS/CdS heterojunction interface, optimizing charge carrier dynamics. Record photoelectrochemical performance including half-cell solar-to-hydrogen (HC-STH) efficiency of 9.91%, photocurrent density of 29.44 mA cm−2 at 0 V RHE in 0.5 M H2SO4 electrolyte, and STH efficiency of 2.20% in CZTS-BiVO4 tandem cell in natural seawater is achieved.